Mathematics  Trigonometric Identities
posted by Anonymous .
Prove:
sinx + tanx = tanx (1 + cosx)
What I have so far:
LS:
= sinx + tanx
= sinx + (sinx / cosx)
= (sinx) (cosx) + sinx / cos
= tanx (cosx + sinx)
I don't know what to do now

Your second last line needs brackets, and the following line makes no sense
Why not work on the right side?
RS = tanx(1+cosx)
=tanx + tanxcosx after expanding
= tanx + (sinx/cosx)cosx
= tanx + sinx
= LS 
My second last line:
(sinx) (cosx) + sinx
_________________________
cosx
When I did the right side, I get the same problem as the left side:
RS:
= tanx + (1 + cosx)
= (sinx / cosx) (1 + cosx)
= (1 + cosx) (cosx)
= (sinx) (1 + cosx)
_______________________
cosx
= (sinx) + (cosx)(sinx)
________________________
cosx
And ... my teacher wants everything in terms of cos and sin 
RS = tanx(1+cosx)
=tanx + tanxcosx after expanding
= tanx + (sinx/cosx)cosx
= tanx + sinx
= LS
For this line "=tanx + tanxcosx after expanding", how did you get the second tanx from and what has happened to the addition sign? 
from you second last line
(sinx) (cosx) + sinx
_________________________
cosx
= sinx[cosx + 1]/cosx , ....I took out a common factor
= tanx(cosx + 1)
= RS
You said "And ... my teacher wants everything in terms of cos and sin"
your teacher probably suggested changing everything to sines and cosines as you work your way through. Notice that is also what I did as I showed the steps.
I would never have restricted my students to use only a part of their trig knowledge, why not make use of all the relationships at your hand, picking the simplest way? 
secx/sinx  sinx/cosx = cotx
Respond to this Question
Similar Questions

PreCalc
Trigonometric Identities Prove: (tanx + secx 1)/(tanx  secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x  1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1  cosx)/cosx)/((sinx … 
Simplifying with Trigonometry Identities
Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each other. … 
Trigonometry.
( tanx/1cotx )+ (cotx/1tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side … 
Trig........
I need to prove that the following is true. Thanks (cosx / 1sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1sinx) multiply top and … 
Mathematics  Trigonometric Identities
Prove: (tanx)(sinx) / (tanx) + (sinx) = (tanx)  (sinx) / (tanx)(sinx) What I have so far: L.S. = (sinx / cosx) sinx / (sinx / cosx) + sinx = (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx) = (sin^2x / cosx) / (cosx / sinx + sinxcosx) 
maths  trigonometry
I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the second. … 
Trigonometry Check
Simplify #3: [cosxsin(90x)sinx]/[cosxcos(180x)tanx] = [cosx(sin90cosxcos90sinx)sinx]/[cosx(cos180cosx+sinx180sinx)tanx] = [cosx((1)cosx(0)sinx)sinx]/[cosx((1)cosx+(0)sinx)tanx] = [cosxcosxsinx]/[cosx+cosxtanx] = [cosx(1sinx]/[cosx(1+tanx] … 
Math
Im really struggling with these proving identities problems can somebody please show me how to do these? 
Math
I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx  cos^2x)/(1 … 
Precalculus/Trig
Prove the following identity: 1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake somewhere: Converted 1/tanx: 1/sinx/cosx + sinx/cosx = 1/sinxcosx Simplified 1/sinx/cosx: cosx/sinx + sinx/cosx …